Sailing into the past learning from replica ships - Bennett, Jenny (Naval Institute Press, 2009)
Until recently, there was little practical knowledge of the ships of the distant past. We could only surmise as to the manner in which a Viking ship sailed or how fast a Greek trireme could be rowed. The building of accurate replicas over the past generation has changed all that, and what has been learnt about the ships and boats of our ancestors has radically changed our perceptions of sailing and voyaging. This beautifully-illustrated new book charts those discoveries. The world's leading authorities look at individual replicas and discuss what they have taught us. Boris Rankov and John Coates, for example, discuss the Greek trireme, while Antonia Macarthur outlines the lessons learnt on Cook's Endeavour. Each chapter deals with a particular vessel and construction, sail plans, and the intended role are covered before an analysis of sailing performance is discussed. Windward ability, seakindliness, speed and ease of handling are all dealt with. General chapters by Richard Woodman and Sean McGrail set the scene.A fascinating work which offers the most accessible view yet as to how the ships of our seafaring forbears affected the manner in which they traded, fought and explored.